CBDC's Considerations on the Islamic Microeconomic: Maqashid Sharia Perspective - Suryaman, Inge Salsabila; Simanullang, Ricky Martin (Universitas Islam Negeri Sunan Gunung Djati Bandung, 2025)
This study aims to analyze the potential impact of Central Bank Digital Currency (CBDC) on Islamic microeconomics, specifically from the perspective of Maqashid Shariah. The study employs a qualitative method with data collection techniques involving a literature review from secondary sources related to CBDC and Islamic economics. The findings indicate that the implementation of CBDC can bring benefits in the form of increased financial inclusion, transaction efficiency, and protection of privacy and payment system integrity. This research contributes to explaining how CBDC can support Islamic economic objectives through fair market competition and technological openness.